2020
DOI: 10.3390/cancers12102748
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Aberrant Claudin-6 Expression in Endometrial Cancer

Abstract: Background: Among the claudin (CLDN) family, CLDN6 exhibits aberrant expression in various cancers, but its biological relevance has not yet been established. We generated a monoclonal antibody (mAb) against human CLDN6 and verified its specificity. By immunohistochemical staining and semi-quantification, we evaluated the relationship between CLDN6 expression and clinicopathological parameters in tissues from 173 cases of endometrial cancer. Results: The established mAb selectively recognized CLDN6 protein. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 34 publications
7
28
0
Order By: Relevance
“…Since then, we confirmed clinical stage, primary therapy outcome, and CLDN6 expression level as independent risk factors in OS, DSS, and PFI of UCEC through univariate and multivariate Cox regression analyses. The results are further supported by the prior research involving prognostic significance of aberrant CLDN6 expression in UCEC ( Kojima et al, 2020 ), which established a monoclonal antibody, then performed immunohistochemical staining and semi-quantification to assess the associations between CLDN6 and clinical characteristics in 173 cases, and finally identified stages III/IV, distant metastasis, and high CLDN6 expression as independent prognostic variables for the OS. It is of great importance that our findings provide a more comprehensive and further supplement and strengthen the role of CLDN6 played in UCEC, and that we precisely analyze the correlations between CLDN6 expression and different prognosis conditions (OS, DSS, or PFI) in various clinical subgroups of UCEC.…”
Section: Discussionsupporting
confidence: 63%
“…Since then, we confirmed clinical stage, primary therapy outcome, and CLDN6 expression level as independent risk factors in OS, DSS, and PFI of UCEC through univariate and multivariate Cox regression analyses. The results are further supported by the prior research involving prognostic significance of aberrant CLDN6 expression in UCEC ( Kojima et al, 2020 ), which established a monoclonal antibody, then performed immunohistochemical staining and semi-quantification to assess the associations between CLDN6 and clinical characteristics in 173 cases, and finally identified stages III/IV, distant metastasis, and high CLDN6 expression as independent prognostic variables for the OS. It is of great importance that our findings provide a more comprehensive and further supplement and strengthen the role of CLDN6 played in UCEC, and that we precisely analyze the correlations between CLDN6 expression and different prognosis conditions (OS, DSS, or PFI) in various clinical subgroups of UCEC.…”
Section: Discussionsupporting
confidence: 63%
“…We have recently reported that aberrant CLDN6 expression in endometrial cancer tissues is significantly associated with several clinicopathological variables, such as surgical stage III/IV, histological type, histological grade 3, lymphovascular space involvement, lymph node metastasis, and distant metastasis. 82 Additionally, we showed that the high CLDN6 expression in endometrial cancer represents an independent prognosis marker, and the 5-y survival rate was approximately 30%, which was one-third of that in the low-expression group.…”
Section: Aberrant Cldn–transcription Factor Signaling In Cancermentioning
confidence: 79%
“…CLDN6 had been demonstrated abnormal expression and can be a prognostic marker in cancers including ovarian cancer ( Wang et al, 2013 ), endometrial cancer ( Kojima et al, 2020 ), gastric cancer ( Kohmoto et al, 2020 ), breast carcinoma ( Liu et al, 2016 ; Jia et al, 2019 ), and lung cancer ( Micke et al, 2014 ). Bioinformatic analysis has revealed that CLDN6 is regulated by a diverse set of transcription factors and promotes cancer cell behavior via the ASK1-p38/JNK MAPK secretory signaling pathway ( Lin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%